Extra views on structure and dynamics of DNA loops on nucleosomes studied with molecular simulations. (1st November 2016) - Pasi, Marco; Angelov, Dimitar; Bednar, Jan; Dimitrov, Stefan; Lavery, Richard
ABSTRACT: It has been shown experimentally that the action of the RSC chromatin remodeler leads to the formation of an irregular, partially remodeled nucleosome, termed a remosome. The remosome contains an extra 30–40 base pairs of DNA compared to a canonical nucleosome. Large-scale molecular simulations have provided information on the probable structure of remosomes and have explained why they remain stable in the absence of RSC. Here we explain how these simulations were carried out and what the resulting remosome models imply in terms of the mechanism of action of RSC. We notably show that local kinks within DNA are key in explaining how extra DNA can be in added to nucleosomes without unduly disturbing DNA-histone binding.